2022
DOI: 10.1038/s41596-022-00737-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience robotics for controlled induction and real-time assessment of hallucinations

Abstract: Although hallucinations are important and frequent symptoms in major psychiatric and neurological diseases, little is known about their brain mechanisms. Hallucinations are unpredictable and private experiences, making their investigation, quantification and assessment highly challenging. A major shortcoming in hallucination research is the absence of methods able to induce specific and short-lasting hallucinations, which resemble clinical hallucinations, can be elicited repeatedly and vary across experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 79 publications
0
35
0
Order By: Relevance
“…Extending our sensorimotor procedure that has been shown to induce PH in healthy subjects (Bernasconi et al, 2022; Blanke et al, 2014; Dhanis et al, 2022; Orepic et al, 2021; Serino et al, 2021) and patients with Parkinson’s disease (Bernasconi et al, 2021), we here demonstrate a new experimental paradigm able to induce controlled AVH-like phenomena (manifested as specific false alarms) in healthy, non-hallucinating individuals. Previous methods of inducing hallucinations in healthy individuals – such as through psychedelic medications (Preller and Vollenweider, 2018) or by automatized visual stimulations (e.g., Flicker-induced (Allefeld et al, 2011; Pearson et al, 2016)) – have identified many important challenges present in hallucination engineering.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Extending our sensorimotor procedure that has been shown to induce PH in healthy subjects (Bernasconi et al, 2022; Blanke et al, 2014; Dhanis et al, 2022; Orepic et al, 2021; Serino et al, 2021) and patients with Parkinson’s disease (Bernasconi et al, 2021), we here demonstrate a new experimental paradigm able to induce controlled AVH-like phenomena (manifested as specific false alarms) in healthy, non-hallucinating individuals. Previous methods of inducing hallucinations in healthy individuals – such as through psychedelic medications (Preller and Vollenweider, 2018) or by automatized visual stimulations (e.g., Flicker-induced (Allefeld et al, 2011; Pearson et al, 2016)) – have identified many important challenges present in hallucination engineering.…”
Section: Discussionmentioning
confidence: 83%
“…In our two studies with two independent cohorts, our participants detected voices (either their own or someone else's) presented at individual hearing thresholds in pink noise, while simultaneously experiencing robotic sensorimotor stimulation. We hypothesized that conflicting sensorimotor stimulation leading to a PH (Bernasconi et al, 2022(Bernasconi et al, , 2021Blanke et al, 2014) would lead to an increase in vocal false alarms (i.e., reporting hearing voices in trials with no physical voice present in noise), compared to the stimulation with a weaker sensorimotor conflict, thereby relating our findings with the self-monitoring account. Moreover, we hypothesized that this increase would be modulated by the voice task they are involved in (other-voice detection vs self-voice detection), being especially prominent when performing other-voice detection.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations